2002
DOI: 10.1074/jbc.m207239200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Inhibition of the Biosynthesis of Biotin by the Antibiotic Amiclenomycin

Abstract: The antibiotic amiclenomycin blocks the biosynthesis of biotin by inhibiting the pyridoxal-phosphate-dependent enzyme diaminopelargonic acid synthase. Inactivation of the enzyme is stereoselective, i.e. the cis isomer of amiclenomycin is a potent inhibitor, whereas the trans isomer is much less reactive. The crystal structure of the complex of the holoenzyme and amiclenomycin at 1.8 Å resolution reveals that the internal aldimine linkage between the cofactor and the side chain of the catalytic residue Lys-274 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 41 publications
(42 reference statements)
6
40
0
Order By: Relevance
“…Inactivation of Escherichia coli DAPA AT by amiclenomycin and analogues was carefully studied using different approaches and was shown to be irreversible with the formation of an aromatic PLP-amiclenomycin adduct 2 that is tightly bound to the active site (Scheme 3) [8][9][10]. The natural cis-amiclenomycin 1a was much more efficient than the trans compound 1b, confirming our stereochemical assignment.…”
Section: Inhibition Of 78-diaminopelargonic Acid Aminotransferase Bysupporting
confidence: 76%
“…Inactivation of Escherichia coli DAPA AT by amiclenomycin and analogues was carefully studied using different approaches and was shown to be irreversible with the formation of an aromatic PLP-amiclenomycin adduct 2 that is tightly bound to the active site (Scheme 3) [8][9][10]. The natural cis-amiclenomycin 1a was much more efficient than the trans compound 1b, confirming our stereochemical assignment.…”
Section: Inhibition Of 78-diaminopelargonic Acid Aminotransferase Bysupporting
confidence: 76%
“…Inhibition studies of E. coli DAPAS by amiclenomycin indicated that the inhibitor binds to the 7-keto-8-aminopelargonic acid/7,8-diaminopelargonic acid binding site of the enzyme [421]. The crystal structures of the complexes formed between the E. coli holoenzyme and cis and trans amiclenomycin have been determined [422]. The structure analysis revealed that the inhibitor forms a covalent adduct with the cofactor PLP, which mimics the external aldimine.…”
Section: Alliinasementioning
confidence: 98%
“…glycine acid) [391] 1K7F, 1.90 (N-[1H-indol-3-yl-acetyl] valine acid) [391] 7,8-diaminopelargonic acid synthase (I) 1QJ5, 1.80 [417] 1QJ3, 2.70 (7-keto-8-aminopelargonic acid) [417] 1MLZ, 2.15 (trans-amiclenomycin) [422] 1MLY, 1.81 (cis-amiclenomycin) [422] 8-amino-7-oxopelargonate synthase (I) 1BS0, 1.65 [429] 1DJ9, 2.00 ((S)-8-amino-7-oxonanonoate) [432] 2G6W, 2.14 (trifluoroalanine adduct) [433] 1DJE, 1.71 [429] early in the evolution (before the three biological kingdoms diverged) from different protein ancestors which generated five independent families, each corresponding to a different fold type [20][21][22]. The families have been named from the more representative enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The BioA inhibitor, amiclenomycin, is a narrow-spectrum antibiotic with activity against Mycobacteria sp., but not other bacteria or fungi that can scavenge exogenous biotin (Kitahara et al, 1975). Its anti-TB activity can be reversed by high concentrations of external biotin, above 0.01 μg/mL (Sandmark et al, 2002;Mann et al, 2005), which is at least 10-fold greater than the concentration found in normal human plasma (Mock and Malik, 1992). This implies that the water-soluble biotin might enter through the bacilli membrane using mechanisms that are not yet identified, but only in supra-physiological concentrations of the nutrient.…”
Section: Biotin Transporter Proteinsmentioning
confidence: 88%